An Approach To Analyze Different Route Factors Using Hadoop Framework - Priya, D. Swetha; khanam, M. Humera (International Journal of Computer Sciences and Engineering, 2018)
Whenever a person travelling from one place to another place. There are different routes between different regions. A person travelling from source to destination chooses a path based on different factors. Route choices from source to destination play an important role. It helps the user to choose the best route from many routes present based on different considerations. The traveller chooses the route with best factors like less time and distance. Such types of route factors are the main reasons to choose the route. We here develop a visual analytic system to display few more route choices. Here, based on the route factors the route with best factors is chosen as the best path and viewed to the user. We study and analyse route factors based on dataset. We analyse the dataset and a system with best and multiple route factors is developed using hadoop Framework.